Protective effect of kaempferol, a flavonoid compound, on oxidative mitochondrial damage in streptozotocin-induced diabetic rats - Chandramohan, Govindasamy; Al-Numair, Khalid S.; Veeramani, Chinnadurai; Alsaif, Mohammed A.; Almajwal, A. Madi (Progress in Nutrition, 2015)
The present study was designed to investigate the effect of kaempferol on oxidative mitochondrial damage in liver of streptozotocin (STZ)-induced diabetic rats. Diabetes was induced into adult male albino rats of the Wistar strain, by intraperitoneal administration of STZ (40 mg/kg body weight (BW)). Kaempferol (100 mg/kg BW) or glibenclamide (600 µg/kg BW) was administered orally once daily for 45 days. Diabetic rats showed a significant elevation of mitochondrial thiobarbituric acid reactive substances (TBARS) levels in liver as compared to control rats. The level of enzymatic (superoxide dismutase (SOD), glutathione peroxidase (GPx)) and non-enzymatic (reduced glutathione (GSH)) antioxidants were decreased significantly in liver mitochondria of STZ-induced diabetic rats as compared to control rats. Administration of kaempferol or glibenclamide resulted in significant decrease in TBARS and significant increase in SOD, GPx and GSH when compared to diabetic control rats. The activities of mitochondrial enzymes such as isocitrate dehydrogenase (ICDH), alpha-ketoglutarate dehydrogenase (α-KGDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH) decreased significantly in STZ-induced diabetic rats. In addition, the activities of mitochondrial respiratory chain enzymes such as NADH dehydrogenase and Cytochrome c-oxidase also decreased significantly in STZ-induced diabetic rats as compared to control rats. Administration of kaempferol or glibenclamide resulted in significant reversal of these enzymes’ activities to near normal when compared to diabetic control rats. Thus, obtained results indicate that administration of kaempferol attenuates the mitochondrial damage in STZ-induced diabetic rats.